Causes, management, and outcomes of polyhydramnios, at a level 2 hospital in Cape Town - Siveregi, Amon (Department of Obstetrics and Gynaecology, 2024)
Introduction: Polyhydramnios is defined as excessive accumulation of amniotic fluid and has an estimated incidence of 0.2% – 3.9%. It is associated with both maternal and fetal adverse outcomes. Mild polyhydramnios is often idiopathic and pregnancy outcomes in this group are usually no worse than in the general population of pregnant women. In contrast, conditions such as congenital anomalies, chromosomal abnormalities, or diabetes mellitus are often found in patients with moderate and severe polyhydramnios. Neonatal and maternal adverse outcomes, can be up to five times higher in this subgroup. Methodology: We conducted a retrospective cohort study at a Level 2 hospital in Cape Town. Folders of women diagnosed with polyhydramnios on ultrasound examination were reviewed. We recorded demographic data as well as information on underlying causes, management and outcomes. We summarised continuous variables using the mean (standard deviation) and categorical variables using count (percentage). We tested the association between categorical variables using the chi-square test. Statistical significance was set at p< 0.05. Results: A total of 136 patients with polyhydramnios (80 mild and 56 moderate + severe) were included from January 1, 2018 to December 31, 2020. Cases of idiopathic polyhydramnios accounted for 81.7% of the mild and 77.2% of the moderate + severe polyhydramnios group. Composite maternal and fetal adverse outcome occurred in 19/136 (14.0 %) polyhydramnios cases. Preterm labour occurrence was significantly higher in the moderate + severe polyhydramnios group (9/56; 16 %) compared to the mild polyhydramnios group (3/80; 3.8%, p = 0.01). There was a statistically significant difference in the occurrence of the composite adverse outcome in the moderate + severe group compared to the mild group [13/56(23.2 %) vs 6/80 (7.5 %) p = 0.001]. Elective delivery at 38 – 40 weeks for polyhydramnios was associated with an increased risk of composite perinatal adverse outcome (7.6% vs 3.4%) compared to those that awaited spontaneous labour or were delivered for other obstetric reasons. The difference was however not statistically significant (p = 0.14). Conclusions: Most cases of polyhydramnios are idiopathic, regardless of category. Adverse outcomes are, however, significantly lower in the mild group compared to the moderate + severe group. The rate of adverse outcome in the mild group is comparable to the background risk in the general population. Elective admission and delivery of patients for polyhydramnios between 38–40 weeks may be associated with adverse outcome compared to awaiting spontaneous labour or delivery indicated for other obstetric reasons.